Modeling, identification and control : a robust and reliable approach to aircraft flight control system design - Wang, Jianliang (2008)
Robustness and reliability are two of the most important properties of all industrial/engineering control systems. This is especially true for aircraft flight control systems. Robustness ensures that the designed control system be able to function properly in the harsh industrial and military environment where system modeling uncertainties and disturbances are very severe. Reliability ensures that the designed systems operate safely in the event of control system component faults/failures. So the controller design methods must be reliable in the sense that the designed controller can still perform even in the presence of certain control system component failures. Hence, how to design control systems that are robust and tolerable of control system component failures are crucial issues facing control engineers.